TO EVALUATE AND COMPARE THE EFFICACY OF LOW LEVEL LASER THERAPY, POTASSIUM OXALATE GEL AND ACIDULATED PHOSPHATE FLUORIDE GEL FOR THE MANAGEMENT OF DENTINAL HYPERSENSITIVITY - DR. PRAGYA TRIPATHI; DR. TOOBA FAREED; DR. PREETI UPADHYAY; DR. NIKITA JAIN; DR. ANUPAMA PRADHAN; DR. TARUN MITTAL (The Bioscan, 2025)
AIM:-To evaluate and compare the efficacy of low level laser therapy, potassium oxalate gel and acidulated phosphate fluoride gel for the management of dentinal hypersensitivity. INTRODUCTION:-Dentinal hypersensitivity (DH) is sharp pain from exposed dentin due to chemical, thermal, or mechanical stimuli, primarily caused by enamel loss and gingival recession. The hydrodynamic theory, which links pain to fluid movement in dentinal tubules, is the most accepted explanation. Treatments aim to reduce dentinal permeability through desensitizing agents, lasers, or tubule-blocking substances like ions, salts, and proteins. This study evaluates the most effective material for DH treatment. OBJECTIVE:-To evaluate and compare pain reduction using VAS with low-level laser therapy, potassium oxalate gel, and acidulated phosphate fluoride gel for dentinal hypersensitivity. METHODOLOGY:-75 sites with dentinal hypersensitivity were included in the study. The selected patients were randomly assigned to one of the treatment groups with 25 sites in each group by computer generated random numbers. Air blast test and cold test were recorded prior to baseline, 1st, 2nd, 3rd and 4th weeks post operatively. RESULT:-For both cold test and air blast test potassium oxalate gel exhibited notably superior progress, compared to the LLLT group and 1.23% APF gel group. However, VAS scores between low-level laser group and the potassium oxalate group showed no significant difference at 3rd and 4th week. CONCLUSION:- All three treatment modalities demonstrated a statistically significant reduction in dentinal hypersensitivity over time, highlighting their potential in managing DH. However, the degree and speed of symptom relief varied among the modalities.